A preliminary model of sweet corn growth and yield. Issue 2 (3rd April 2017) - Reid, J. B.
ABSTRACT: A model is developed to assist forecasting and interpretation of crop performance of sweet corn ( Zea mays L.) under optimal nutrient supply. Leaf area growth is calculated on the main stem and tillers separately using a discrete logistic equation that includes adjustments for soil water deficit ( D ). Leaf senescence depends on age and D . The conversion efficiency for intercepted radiation to biomass also varies with D . Ear dry mass is computed assuming harvest index varies linearly with thermal time. The model was fitted using a dataset for crop responses to D, tested against data for responses to sowing date, refitted using both datasets, and retested against measurements of growth across a wide range of plant populations. Model performance was excellent for leaf area and biomass. It was less good for ear dry mass, although regression of observed on simulated values gave slopes not significantly different from 1. Priorities for further development are discussed.